Gains from Integration? An Empirical Hint from the Eurozone. (26th June 2020) - Chen, Ku-Hsieh; Cheng, Jen-Chi; Lee, Joe-Ming; Chen, Chih-Chun
Abstract : Has the eurozone (EZ) really gained from integration? This study applied two econometric frameworks, mGARCH and gMMPI, to test this hypothesis, using panel data that span 1996–2014, a total of 19 years, involving the EZ, EU, G8, G20 and some emerging economies. The empirical outcomes initially showed that the EZ economies experienced neither superior output growth nor a better capital market return than non-EZ economies or the pre-EZ period. They further suggested that each EZ country had a higher degree of risk bearing and, as a group, a greater risk linkage. Moreover, the results indicated that the EZ had a higher productivity gain if the risk premium was counted as part of productivity. Nonetheless, the EZ did not show a substantial productivity gain when the effect of the risk factor was controlled. The ratio of risk bearing to risk premium gain was shown to be 1 to 0.97. The general conclusion is that, other than the risk premium, there was no extra productivity gain for the EZ from taking the risk.